2001
DOI: 10.1530/eje.0.1440139
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the sodium iodide symporter by iodide in FRTL-5 cells

Abstract: Objective: The acute decrease in iodide organification in the thyroid in response to excess iodide is termed the acute Wolff±Chaikoff effect and normal organification resumes in spite of continued high plasma iodide concentrations (escape from the acute Wolff±Chaikoff effect). We have recently reported that large doses of iodide given to rats chronically decrease the sodium/iodide symporter (NIS) mRNA and protein, suggesting that escape is due to a decrease in NIS and subsequent iodide transport. We have now s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
2
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 18 publications
5
54
2
9
Order By: Relevance
“…The same group studied the effect of high doses of iodide on NIS regulation in FRTL-5 cells. Surprisingly, high doses of iodide during 24 and 48 h did not decrease the NIS mRNA levels, but did decrease the NIS protein levels in a dose-dependent manner, suggesting that in this in vitro thyroid cell model, iodide modulates NIS at a post-transcriptional level (22). These results are in sharp contrast with the previous in vivo study reported by the same authors.…”
Section: Main Factors That Regulate Nis Expressioncontrasting
confidence: 99%
“…The same group studied the effect of high doses of iodide on NIS regulation in FRTL-5 cells. Surprisingly, high doses of iodide during 24 and 48 h did not decrease the NIS mRNA levels, but did decrease the NIS protein levels in a dose-dependent manner, suggesting that in this in vitro thyroid cell model, iodide modulates NIS at a post-transcriptional level (22). These results are in sharp contrast with the previous in vivo study reported by the same authors.…”
Section: Main Factors That Regulate Nis Expressioncontrasting
confidence: 99%
“…Expression of NIS is a marker of differentiated thyroid function, and at least some level of NIS expression is essential for successful therapy of thyroid carcinoma using radioactive iodine ablation (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The utility of NIS immunostaining has been previously studied but only on a limited number of adult thyroid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…NIS is essential for the uptake of iodide and thyroid hormone synthesis and is directly related to the level of thyroid differentiation (5-9). NIS expression is controlled by TSH and dependent on TTF-1 as well as [10][11][12][13][14][15]. Because of the central role of NIS in determining radioactive iodine uptake, it has been postulated that thyroid carcinoma that fail to express NIS would be resistant to radioactive iodine ablation (16).…”
mentioning
confidence: 99%
“…These latter effects are likely to play an important role during pregnancy. Considering that many other factors, including iodide (30), estradiol (31,32) and certain cytokines (11,12), can also modify iodide uptake by acting on NIS expression, and that these factors are themselves subject to pregnancy related modifications, we feel that elucidation of the mechanisms that regulate NIS expression may help to clarify the pathogenesis of a number of thyroid disorders that are associated with pregnancy.…”
Section: Discussionmentioning
confidence: 99%